2018
DOI: 10.1111/fme.12280
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐related variation in the reproductive characteristics of female pikeperch (Sander lucioperca)

Abstract: Maternal characteristics typically affect the recruitment of an exploited fish population. The size and age at maturity, as well as the effects of maternal traits on relative fecundity and egg dry weight, were studied in six exploited pikeperch populations in Finnish lakes. The among‐lake variation in the maternal characteristics was substantial. The estimated total length at maturity (L10, L50, L90) varied between 318–444, 403–423 and 444–527 mm, respectively, largely depending on the average growth rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…The ecological status classification of the lake is good (database of Finnish Environment Institute, SYKE). During the present study, the minimum size limit for pikeperch was 450 mm in Lake Höytiäinen (Olin et al, ).…”
Section: Methodsmentioning
confidence: 65%
“…The ecological status classification of the lake is good (database of Finnish Environment Institute, SYKE). During the present study, the minimum size limit for pikeperch was 450 mm in Lake Höytiäinen (Olin et al, ).…”
Section: Methodsmentioning
confidence: 65%
“…Several studies have been performed in pikeperch concerning productive (e.g., growth and survival) 5 7 and reproductive (e.g., fecundity and spawning) 8 , 9 traits. However, despite the growing commercial importance of this species, little information is available regarding its genetic and genomic makeup.…”
Section: Introductionmentioning
confidence: 99%
“…The species studied by us is the slow-growing pikeperch (Sander lucioperca) in Sahajärvi, a lake in Finland (Vinni et al 2009, Milardi et al 2011. Olin et al (2018) showed that the slow-growing female pikeperch matured at an older age but smaller size than the fast-growing ones. Aside from the growth rate, the first females matured three years earlier than the last ones (Olin et al 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Olin et al (2018) showed that the slow-growing female pikeperch matured at an older age but smaller size than the fast-growing ones. Aside from the growth rate, the first females matured three years earlier than the last ones (Olin et al 2018). Thus, assigning one age at maturation to the entire population is not accu-rate, as it rarely fits all individuals (Lehtonen 1987, Raikova-Petrova & Živkov 1998, Lappalainen et al 2003, Ruuhijärvi et al 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation